2009
DOI: 10.1074/mcp.m800190-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Mass Spectrometry Approach Reveals Human Embryonic Stem Cell Growth Factors in Culture

Abstract: The derivation and long-term maintenance of human embryonic stem cells (hESCs) has been established in culture formats that are both dependent and independent of support (feeder) cells. However, the factors responsible for preserving the viability of hESCs in a nascent state remain unknown. We describe a mass spectrometrybased method for probing the secretome of the hESC culture microenvironment to identify potential regulating protein factors that are in low abundance. Individual samples were analyzed several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 34 publications
4
88
0
Order By: Relevance
“…As the total energy budget was greater in hESCs than in NSCs, this indicated a faster macromolecule synthesis rate in hESCs; however, in the absence of increased cell division, these extra macromolecules must ultimately be degraded or secreted. hESCs have been shown to secrete a diverse range of chemokines, cytokines, growth factors and matrix remodelling enzymes, along with cytosolic and cytoskeletal components (Bendall et al, 2009;LaFramboise et al, 2010). We found that hESCs had morphological indications of goblet-cell-like secretion and secreted significantly more protein into the extracellular environment than did NSCs.…”
Section: Discussionmentioning
confidence: 58%
“…As the total energy budget was greater in hESCs than in NSCs, this indicated a faster macromolecule synthesis rate in hESCs; however, in the absence of increased cell division, these extra macromolecules must ultimately be degraded or secreted. hESCs have been shown to secrete a diverse range of chemokines, cytokines, growth factors and matrix remodelling enzymes, along with cytosolic and cytoskeletal components (Bendall et al, 2009;LaFramboise et al, 2010). We found that hESCs had morphological indications of goblet-cell-like secretion and secreted significantly more protein into the extracellular environment than did NSCs.…”
Section: Discussionmentioning
confidence: 58%
“…5C). Several of these have previously been found in proteomic screens of MEF and hESC-conditioned medium (29). However, their detection in conditioned Matrigel™ suggests that the ECM is playing a role in their activity.…”
Section: Stem Cell Factors Identified In Conditioned Matrigelmentioning
confidence: 99%
“…The total number of overlapping identifications can be found at the top of the bar in text. The rightmost bars in the top graphs of C and D represent total identifications found in Matrigel™ (11) and the H9 hESC secretome (29).…”
Section: Proteomic Analysis Of Pluripotent-stem-cell-derived Conditiomentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the factors presented in the ESCM such as MIF, PAI-1, sICAM-1, IL-6 and IL-8 have been detected in conditioned medium from undifferentiated human H1/H9 (Bendall et al 2009) and Hsf1 ES cell lines (LaFramboise et al 2010). Interestingly, undifferentiated human H1 and H9 ES cell lines could produce bFGF and TGFb1 which have been identified as growth factor for MSCs proliferation.…”
Section: Discussionmentioning
confidence: 99%